Formulasi Model Kepemimpinan Selama Pandemi Covid-19 Pada Pimpinan Bank Mandiri Region Bandung Sebagai Upaya Menjaga Profitabilitas Perusahaan - Riyanto Riyanto; Erie Febrian; John Sihotang (University of Merdeka Malang, 2021)
This study aims to formulate a model of leadership in a strategic management framework referring to the leadership model literature in times of crisis with the results of deep interviews with top leaders in the region. This study uses a qualitative descriptive research approach where this research is a research method that utilizes qualitative data and is described descriptively. The type of research used is descriptive qualitative. The source of data in this study is primary data obtained by conducting questionnaire research in order to become the results and conclusions of the study. Using purposive sampling method. Samples were taken as many as 150 branches with the priority of the above criteria. In this study, it was found that the results of deep interviews and FGDs outline the strategy carried out during the pandemic is a survival strategy or profit strategy where companies seek to find sources of income that can still experience growth such as transactional digital transactions, e-commerce, investment transactions. and minimize the formation of costs arising from the decline in credit quality.